Phosphorus / tin composite materials and heterojunction phosphorus / tin / carbon composite materials and their applications
Through the preparation of phosphorus/tin composite materials and heterojunction phosphorus/tin/carbon composite materials, the poor performance of the negative electrode material of lithium-ion battery is solved, and the Sn3P4/Sn4P3@C-CMC-Na electrode material in lithium-ion batteries is realized. The good cycle and rate performance show significant application prospects.
Patent Information
- Application Number
- CN202110534493.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-05-17
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-05-17
AI Technical Summary
The existing lithium-ion battery negative electrode material Sn3P4 has poor performance and severe capacity attenuation, making it not suitable for the preparation of lithium-ion batteries, and its application in lithium-ion batteries has not yet been studied in depth.
Using phosphorus/tin composite materials and heterojunction phosphorus/tin/carbon composite materials, Sn3P4 material is synthesized through high-temperature solid phase reaction, and ball milling is used in water-based adhesives to form Sn3P4/Sn4P3-CMC-Na and Sn3P4/Sn4P3@C-CMC-Na electrode material.
The good cycle performance and rate performance of the negative electrode materials of lithium-ion batteries have been achieved. In particular, the Sn3P4/Sn4P3@C-CMC-Na electrode materials have significant application prospects, showing good electrochemical performance and high current load capacity.
Smart Images

Figure CN113540443B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular relates to a phosphorus / tin composite material and a heterojunction phosphorus / tin / carbon composite material and applications thereof. Background Art
[0002] Lithium-ion battery is a highly efficient energy storage device that can collect energy from renewable resources. As the most commonly used graphite negative electrode, it has disadvantages such as low capacity, which limits its further and higher demand use. Therefore, the study of negative electrode materials with high capacity and good electrochemical performance is a hot topic in the current research field of lithium-ion battery negative electrodes. In the Sn-P material system, there are several compounds such as Sn4P3, SnP, SnP3, Sn3P4, etc. Among them, as a layered Sn3P4 material with a higher P content (compared to SnP and Sn4P3 materials), only its synthesis and preparation process has been studied, and its application in lithium-ion batteries has not yet been studied. Referring to the performance of Sn4P3 material and the theoretical capacity of Sn3P4 material, it is preliminarily judged that Sn3P4 material has great development potential and strong lithium storage capacity.
[0003] Sn3P4 material has a high current of up to 1517 mA hg -1 , which is four times that of graphite (theoretical capacity is 372mA hg -1 ). Sn3P4 material can be synthesized through a simple high-temperature solid-phase reaction and has a layered crystal structure. It is a new type of negative electrode material for lithium-ion batteries. However, the original Sn3P4 material has poor performance and severe capacity decay, making it unsuitable for the preparation of lithium-ion batteries. Summary of the invention
[0004] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a phosphorus / tin composite material and a heterojunction phosphorus / tin / carbon composite material and applications thereof. The phosphorus / tin composite material and the heterojunction phosphorus / tin / carbon composite material exhibit good electrochemical properties in an aqueous binder and can be used to prepare a negative electrode for a lithium-ion battery.
[0005] The technical solution adopted to achieve the above-mentioned purpose of the present invention is:
[0006] A phosphorus / tin composite material is prepared by the following method:
[0007] Tin powder and phosphorus powder are uniformly mixed, and the molar ratio of tin powder to phosphorus powder is 1:2 to 1:1 to obtain a mixed powder. The mixed powder is placed in a quartz tube under a vacuum state, the quartz tube is sealed, and the quartz tube is placed in a high-temperature tube furnace for high-temperature solid-phase reaction. The temperature is increased to 420-460°C by a gradient program heating method, and the heating rate is 2-3°C / min. The temperature is kept at 420-460°C for 3-7 days. After the reaction is completed, the quartz tube is directly taken out for quenching and cooling, and the solid matter in the quartz tube is taken out to obtain the phosphorus / tin composite material.
[0008] A heterojunction phosphorus / tin / carbon composite material is prepared by the following method:
[0009] In an inert gas atmosphere, a phosphorus / tin composite material and conductive carbon black are mixed and then ball-milled. The mass ratio of the phosphorus / tin composite material to the conductive carbon black is 7:3 to 9:1. After ball-milling, the mixture is allowed to stand to reduce the activity of the mixture. After standing, a heterojunction phosphorus / tin / carbon composite material is obtained.
[0010] Furthermore, the standing time is 15-24 hours.
[0011] Furthermore, in the ball milling operation, the ball milling is performed to a particle size distribution of 10-20 μm.
[0012] Application of phosphorus / tin composite materials and heterojunction phosphorus / tin / carbon composite materials in the preparation of lithium-ion battery negative electrodes.
[0013] Furthermore, when preparing the negative electrode of the lithium ion battery, the binder is an aqueous binder.
[0014] Furthermore, the water-based binder is sodium carboxymethyl cellulose.
[0015] Further, the preparation method of the negative electrode of the lithium ion battery is as follows:
[0016] The phosphorus / tin composite material or heterojunction phosphorus / tin / carbon composite material, conductive carbon black and aqueous binder solution are uniformly mixed, and the mass ratio of the heterojunction tin phosphide composite material, conductive carbon black and aqueous binder solution is 7:2:1 to obtain electrode slurry, and the electrode slurry is coated on copper foil and dried to obtain the lithium ion battery negative electrode.
[0017] Furthermore, the mass percentage concentration of the water-based binder is 2.5%.
[0018] Compared with the prior art, the beneficial effects and advantages of the present invention are:
[0019] When the phosphorus / tin composite material and heterojunction phosphorus / tin / carbon composite material prepared by the present invention are used to prepare lithium ion negative electrodes, an aqueous binder is used, and the obtained Sn3P4 / Sn4P3-CMC-Na electrode and Sn3P4 / Sn4P3@C-CMC-Na electrode have good cycle performance and rate performance, especially the Sn3P4 / Sn4P3@C-CMC-Na electrode. Therefore, these two electrode materials have good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the SEM image of Sn3P4 / Sn4P3 prepared in Example 1.
[0021] Figure 2 This is the HR-TEM image of Sn3P4 / Sn4P3 prepared in Example 1 (the inset is the SAED image).
[0022] Figure 3 This is the SEM image of Sn3P4 / Sn4P3@C prepared in Example 1.
[0023] Figure 4 HR-TEM image of Sn3P4 / Sn4P3 prepared in Example 1: Figure 4 (a) is the HR-TEM image of Sn3P4 / Sn4P3@C (the inset is the SAED image). Figure 4 (b) The edge of Sn3P4 / Sn4P3@C
[0024] Figure 5 This is the XRD pattern of Sn3P4 / Sn4P3 prepared in Example 1.
[0025] Figure 6 This is the XRD pattern of Sn3P4 / Sn4P3@C prepared in Example 1.
[0026] Figure 7 This is the Raman spectrum of Sn3P4 / Sn4P3@C prepared in Example 1.
[0027] Figure 8 This is the cyclic voltammetry curve of the Sn3P4 / Sn4P3-CMC-Na electrode prepared in Example 2.
[0028] Fig. 9 The cycle stability performance diagram of the Sn3P4 / Sn4P3-CMC-Na electrode prepared in Example 2: Fig. 9 (a) is the cycle stability performance diagram measured under low current conditions; Fig. 9 (b) is the cycle stability performance diagram measured under high current conditions.
[0029] Fig.10This is the rate performance diagram of the Sn3P4 / Sn4P3-CMC-Na electrode prepared in Example 2.
[0030] Fig.11 This is the cyclic voltammetry curve of the Sn3P4 / Sn4P3@C-CMC-Na electrode prepared in Example 3.
[0031] Fig.12 The cycle stability performance diagram of the Sn3P4 / Sn4P3@C-CMC-Na electrode prepared in Example 3: Fig.12 (a) is the cycle stability performance diagram measured under low current conditions; Fig.12 (b) is the cycle stability performance diagram measured under high current conditions.
[0032] Fig.13 This is the rate performance diagram of the Sn3P4 / Sn4P3@C-CMC-Na electrode prepared in Example 2.
[0033] Fig.14 This is the cyclic voltammetry curve of the Sn3P4 / Sn4P3-PVDF electrode prepared in Comparative Example 1.
[0034] Fig.15 The cycle stability performance diagram of the Sn3P4 / Sn4P3-PVDF pole piece prepared in Comparative Example 1: Fig.15 (a) is the cycle stability performance diagram measured under low current conditions; Fig.15 (b) is the cycle stability performance diagram measured under high current conditions.
[0035] Fig.16 This is the rate performance diagram of the Sn3P4 / Sn4P3-PVDF pole piece prepared in Comparative Example 1. DETAILED DESCRIPTION
[0036] The present invention is described in detail below with reference to specific embodiments.
[0037] Example 1
[0038] 1. Weigh 0.5g of tin powder and phosphorus powder on an electronic balance, including 0.3710g of tin powder and 0.1290g of phosphorus powder. Mix the tin powder and phosphorus powder evenly on weighing paper to obtain a mixed powder. Then use a manual powder tablet press to press the mixed powder into a thin disc with a diameter of 15mm at a pressure of 20MPa to make the reaction more sufficient to achieve the purpose of obtaining the target material. Put the thin disc into a clean quartz tube, and then use a vacuum tube sealer to extract the air inside the quartz tube to make the inside of the quartz tube The quartz tube is in a vacuum state, and then the quartz tube is sealed with a quartz plug under the action of a high-temperature flame, and then the quartz tube is placed in a high-temperature tube furnace for a high-temperature solid-phase reaction, and a gradient temperature control program is set. The temperature is raised from room temperature to 460°C in 3 hours, and the heating rate is 2.4°C / min. The temperature is kept at 460°C for 7 days. After the reaction is completed after 7 days, the quartz tube is directly taken out and placed in pre-prepared cold water for quenching and cooling. The thin disc in the quartz tube is taken out to obtain a phosphorus / tin composite material, which is recorded as Sn3P4 / Sn4P3;
[0039] 2. Weigh 0.25 g of Sn3P4 / Sn4P3 and conductive carbon black Super P on an electronic balance, of which 0.2 g is Sn3P4 / Sn4P3 and 0.05 g is conductive carbon black Super P. Mix Sn3P4 / Sn4P3 and carbon black evenly and pour them into a ball mill with a diameter of 15 mm. Put a 1.0 g small ball mill bead into the ball mill. Replace the air inside the ball mill with argon gas through an argon glove box to prevent oxidation of the solid matter in the ball mill. Then seal the ball mill with tape, and then place the ball mill on a SPEX-8000M ball mill. Set the ball milling time to 30 min. After the ball milling is completed, put the ball mill into an argon glove box and let it stand overnight to reduce the activity of the solid matter in the ball mill. Take out the solid matter in the ball mill the next day to obtain a heterojunction phosphorus / tin / carbon composite material, marked as Sn3P4 / Sn4P3@C.
[0040] The Sn3P4 / Sn4P3 prepared in this example was scanned by a scanning electron microscope at different magnifications. The obtained SEM images are shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the macroscopic morphology of the material can be observed under 5k and 10k magnifications, and the overall structure is aggregated block-like. At a larger magnification of 20k, it can be seen that the material has an obvious layered structure, which indicates that the Sn3P4 / Sn4P3 prepared in this embodiment is composed of thin layered stacks.
[0041] The Sn3P4 / Sn4P3 prepared in this example was scanned by a high-resolution transmission electron microscope at different magnifications. The obtained HR-TEM images are shown in Figure 2 As shown, from Figure 2It can be seen that the HRTEM image shows the lattice fringes on the surface of the Sn3P4 / Sn4P3 layered material. By measuring its interplanar spacing (0.221nm), it is determined that the exposed crystal plane of the Sn3P4 / Sn4P3 material is the (110) crystal plane (JCPDS 01-076-7121). The inset is the SAED image of the same layer area. The diffraction spots of SAED correspond to the (121), (211) and (1-10) crystal planes of Sn3P4, respectively. The calculated crystal zone axis is (11-3), of which the (1-10) crystal plane is the same family as the (110) crystal plane in HR-TEM and has the same interplanar spacing.
[0042] The Sn3P4 / Sn4P3@C prepared in this example was scanned by a scanning electron microscope at different magnifications. The obtained SEM images are shown in Figure 3 As shown, from Figure 3 It can be seen that the original layered morphology has been covered, some parts of the Sn3P4 / Sn4P3 material surface are covered with some nano-microspheres, and some parts form a uniform film covering the material surface under the action of high-energy ball milling, which is presumed to be carbon black Super P, which was later verified by Raman characterization.
[0043] The Sn3P4 / Sn4P3@C prepared in this example was scanned by a high-resolution transmission electron microscope at different magnifications. The obtained HR-TEM images are shown in Figure 4 As shown, Figure 4 The lattice fringes on the interface and surface of Sn3P4 / Sn4P3@C material are shown. The calculation shows that the exposed interplanar spacing of Sn3P4 / Sn4P3@C material is 0.221nm, corresponding to the (110) crystal plane of Sn3P4. Figure 4 In (b), it can also be observed that the edge of the Sn3P4 / Sn4P3 material is uniformly coated with conductive carbon black Super P. In addition, the SAED image corresponding to the inset observed the (121), (211), and (110) crystal planes of Sn3P4, which is consistent with the HR-TEM results.
[0044] The Sn3P4 / Sn4P3 prepared in this example was subjected to XRD analysis, and the obtained XRD pattern is as follows: Figure 5 As shown, from Figure 5It can be seen that by comparing the XRD test results with the standard card (Sn3P4, JCPDS 01-076-7121), the main diffraction peaks of the Sn3P4 / Sn4P3 material are in good agreement with the standard card, and can completely match the (006), (101), (104), (015), (009), (1010), (110), (205), and (119) crystal plane diffraction peaks of the Sn3P4 material, wherein the diffraction peak at 29° is the main peak of the material, and has a high peak intensity and a narrow peak width. This proves that the present invention synthesizes a material whose main phase is Sn3P4 by high-temperature solid phase reaction using red phosphorus and tin powder single-substance raw materials. In addition, we note that there are several diffraction peaks near the 31° diffraction angle that are obviously not Sn3P4. After analysis and comparison, it is proved to be Sn4P3 material (JCPDS 01-071-2221).
[0045] The Sn3P4 / Sn4P3@C prepared in this example was subjected to XRD analysis, and the obtained XRD pattern is shown in Figure 6 As shown, from Figure 6 It can be seen that the diffraction peaks of Sn3P4 / Sn4P3@C materials are consistent with the standard peaks of Sn3P4 and Sn4P3 materials. No obvious diffraction peaks of carbon black Super P were observed. This may be because ball milling destroys the crystal structure of carbon black, causing it to tend to form an amorphous state. The amorphous peaks are easily blocked by the diffraction peaks of Sn3P4 / Sn4P3 materials in the XRD image. Therefore, we further verified the existence of the carbon component through Raman spectroscopy.
[0046] The Sn3P4 / Sn4P3 and Sn3P4 / Sn4P3@C prepared in this example were subjected to Raman spectroscopy analysis. The obtained Raman spectra are as follows: Figure 7 As shown, from Figure 7 It can be seen that compared with Sn3P4 / Sn4P3 material, the Raman spectrum of Sn3P4 / Sn4P3@C material coated with carbon black Super P clearly has carbon D band and G band, which are located at 1357cm -1 and 1602cm -1 The peak of the D band is caused by amorphous carbon, and the peak of the G band is caused by graphitized carbon. The peak intensity ratio of the D band to the G band is about 0.99, which proves that the carbon in the material exists in two forms: graphitized state and amorphous state. The presence of carbon is beneficial to improving the conductivity and stability of the active material.
[0047] Example 2
[0048] 1. Weigh 0.14 g Sn3P4 / Sn4P3 prepared in Example 1, 0.04 g carbon black Super P and 0.8 g CMC-Na solution with a concentration of 2.5% using an electronic balance, mix them evenly to obtain a solid-liquid mixture, transfer the solid-liquid mixture to a weighing bottle, place the weighing bottle on a magnetic stirrer and stir for 4 h to obtain a uniform viscous slurry;
[0049] 2. Clean the copper foil with anhydrous ethanol, transfer the slurry to the copper foil, use a four-sided preparation device and select an appropriate thickness according to the viscosity, and evenly coat the slurry on the copper foil. Then put the copper foil coated with the film in a vacuum drying oven, bake it in air at 80°C for 2 hours without vacuuming to prevent wrinkles in the film, and then bake it at 80°C under vacuum conditions for 12 hours. After drying, use a manual buckle machine to make the copper foil into a circular electrode sheet with a diameter of 12 mm, recorded as Sn3P4 / Sn4P3-CMC-Na electrode sheet, and use an electronic balance to weigh and record the mass of each Sn3P4 / Sn4P3-CMC-Na electrode sheet.
[0050] The Sn3P4 / Sn4P3-CMC-Na electrode prepared in this example was tested by cyclic voltammetry with a voltage range of 0.005-1.2 V and a scan rate of 0.1 mV s -1 Before testing, the battery was left to stand for 24 hours to allow the electrolyte inside the battery to evenly infiltrate other components and eliminate polarization to obtain accurate measurement results. The resulting cyclic voltammetry curve is shown in Figure 8 As shown, from Figure 8 Analyzing the CV curve of Sn3P4 / Sn4P3-CMC-Na negative electrode, in the first cycle of discharge, a relatively gentle reduction peak first appeared at around 0.8V, which corresponds to Li + During the reaction process of embedding into Sn3P4 material, Li2Sn3P4 phase is generated. In the subsequent CV cycles, the reduction peak becomes more obvious and convex, proving that Li + The embedding process of Sn3P4 / Sn4P3-PVDF electrode is better and more complete. It is observed that a sharp reduction peak appears at about 0.52V, which only appears in the first cycle and disappears in the subsequent CV cycles. From the previous analysis, it is known that this peak corresponds to the formation of SEI film. The reduction peak at about 0.24V is the further reaction of the previously generated Li2Sn3P4. First, Sn and LiP are generated, and then Sn and Li + The reaction generates Li 4.4 Sn alloys, LiP and Li + The reaction generates Li3P. In the subsequent CV cycles, the peak splits into two reduction peaks, one at 0.26V, which corresponds to Li 4.4The peak of Sn alloy is shifted to the right relative to 0.24V, which proves that the difficulty of its reaction is slightly increased and a larger voltage is required for the reaction to occur. The other peak at 0.50V corresponds to the formation of Li3P phase. For the charging process, the oxidation peaks at 0.51V and 0.88V correspond to Li 4.4 The dealloying process of Sn and the decomposition reaction of Li3P. This material has two phases, Sn3P4 and Sn4P3, of which Sn3P4 is the main phase and the Sn4P3 phase is less. The reaction is more complicated, and the reaction process of the Sn4P3 phase is not analyzed for the time being.
[0051] The Sn3P4 / Sn4P3-CMC-Na electrode prepared in this example was subjected to a cycle stability test at a voltage range of 0.005-1.2 V and a current of 0.1 A g -1 Under these conditions, the obtained cycle stability performance diagram is shown in Fig. 9 As shown in (a), analysis Fig. 9 (a) It is known that the first cycle discharge capacity of Sn3P4 / Sn4P3-CMC-Na negative electrode is 1332 mA h g -1 , charging capacity is 1085mA hg -1 The first cycle coulombic efficiency is 81%. Compared with comparative example 1, the Sn3P4 / Sn4P3-PVDF electrode has improved, indicating that the irreversible capacity loss caused by the formation of SEI film in the first cycle has decreased, showing good cycle reversibility. After 100 cycles of charge and discharge, the Sn3P4 / Sn4P3-CMC-Na negative electrode maintains a high discharge / charge capacity of 332 mA h g -1 (25% of the first cycle discharge capacity) and 325mA hg -1 (30% of the first cycle charge capacity). Compared with comparative example 1, the Sn3P4 / Sn4P3-PVDF negative electrode at 0.1Ag -1 65mA hg after 100 cycles under current -1 The performance of Sn3P4 / Sn4P3-CMC-Na negative electrode has been improved by more than 5 times, which is a significant improvement. It can be seen that Sn3P4 / Sn4P3-CMC-Na negative electrode has good electrochemical performance. The Sn3P4 / Sn4P3-CMC-Na negative electrode has good electrochemical performance, mainly because: (1) The aqueous binder CMC-Na is a material with good elasticity, good ductility and long-lasting stress adaptability, which can adapt to the repeated insertion and extraction of Li +(2) Under the action of aqueous binder, the heterojunction region in Sn3P4 / Sn4P3 material has better reaction activity, which promotes the ion transmission speed; (3) Sn3P4 / Sn4P3 material itself has a complete layered structure, and its potential has been effectively exerted in CMC-Na. The layered structure effectively shortens the Li + The transmission path speeds up the transmission rate.
[0052] The Sn3P4 / Sn4P3-CMC-Na electrode prepared in this example was subjected to a cycle stability test with a voltage range of 0.005-1.2 V and a current of 0.1 A g in the first three cycles. -1 , then 1A g -1 Under these conditions, the obtained cycle stability performance diagram is shown in Fig. 9 As shown in (b), analysis Fig. 9 (b) It can be seen that the first cycle discharge capacity of Sn3P4 / Sn4P3-CMC-Na electrode is 1328 mA h g -1 , in the third cycle there is more than 800mA hg -1 Then when the current is increased to 1A g -1 , the discharge capacity of Sn3P4 / Sn4P3-CMC-Na negative electrode decreased to 718 mA h g -1 This value is much higher than that of Comparative Example 1, Sn3P4 / Sn4P3-PVDF 120mA hg -1 The discharge capacity of the battery was 414 mA hg after 100 cycles. -1 、406mA hg -1 The high discharge / charge capacity was maintained in the fourth cycle (the current was increased to 1A g -1 ) discharge capacity is 57%. This shows that under high current, the morphology and structure of Sn3P4 / Sn4P3-CMC-Na material are well maintained. + The de-embedding is not affected much and thus performs better.
[0053] The good large current charge and discharge performance of Sn3P4 / Sn4P3-CMC-Na electrode proves that the superior lithium storage potential of 2D layered Sn3P4 / Sn4P3 material has been effectively exerted in the CMC-Na aqueous binder system.
[0054] The Sn3P4 / Sn4P3-CMC-Na electrode prepared in this example was tested for its rate performance at 0.1Ag. -1 , 0.2A g -1 , 0.5A g -1 , 1A g-1 , 2A g -1 The charge and discharge capacity at the same current is cycled 5 times at each current, and the resulting rate performance diagram is as follows Fig.10 As shown, it is first observed that, compared with Comparative Example 1, the rate performance of Sn3P4 / Sn4P3-PVDF electrode and Sn3P4 / Sn4P3-CMC-Na electrode has a slower decline, showing better performance. -1 , 0.2A g -1 , 0.5A g -1 , 1Ag -1 The discharge capacity under current is 947mA hg -1 、834mA hg -1 、610mA hg -1 、411mA hg -1 When the current increases to 2A g -1 , the electrode maintains 171mA hg -1 This discharge capacity. When the current returns to 0.1A g -1 , its discharge capacity recovered to 725mA hg -1 . This proves that under gradually increasing current, the internal polarization of the Sn3P4 / Sn4P3-CMC-Na electrode is alleviated compared with the Sn3P4 / Sn4P3-PVDF electrode in comparative example 1, and the charge and discharge are more complete. Therefore, the Sn3P4 / Sn4P3-CMC-Na electrode has better rate performance.
[0055] Example 3
[0056] 1. Use an electronic balance to weigh 0.14 g of Sn3P4 / Sn4P3@C prepared in Example 1, 0.04 g of carbon black Super P and 0.8 g of 2.5% CMC-Na solution, mix them evenly to obtain a solid-liquid mixture, transfer the solid-liquid mixture to a weighing bottle, place the weighing bottle on a magnetic stirrer and stir for 4 h to obtain a uniform viscous slurry;
[0057] 2. Clean the copper foil with anhydrous ethanol, transfer the slurry to the copper foil, use a four-sided preparation device and select an appropriate thickness according to the viscosity, and evenly coat the slurry on the copper foil. Then put the copper foil coated with the film in a vacuum drying oven, bake it in air at 80°C for 2 hours without vacuuming to prevent wrinkles in the film, and then bake it at 80°C under vacuum conditions for 12 hours. After drying, use a manual buckle machine to make the copper foil into a circular electrode sheet with a diameter of 12 mm, recorded as Sn3P4 / Sn4P3@C3-CMC-Na electrode sheet, and use an electronic balance to weigh and record the mass of each Sn3P4 / Sn4P3@C-CMC-Na electrode sheet.
[0058] The Sn3P4 / Sn4P3@C-CMC-Na electrode prepared in this example was tested by cyclic voltammetry with a voltage range of 0.005-1.2 V and a scan rate of 0.1 mV s -1 Before testing, the battery was left to stand for 24 hours to allow the electrolyte inside the battery to evenly infiltrate other components and eliminate polarization to obtain accurate measurement results. The resulting cyclic voltammetry curve is shown in Fig.11 As shown, analysis Fig.11 The CV curve of Sn3P4 / Sn4P3@C-CMC-Na electrode shows that during the first discharge cycle, a corresponding Li + The reduction peak of the material embedded in Sn3P4 / Sn4P3 to generate Li2Sn3P4 phase appears earlier, has a larger range, and is smoother than that of the two electrodes in Example 2 and Comparative Example 1, indicating that the Li + More, and the embedding process is smoother, and the morphology and structure of the Sn3P4 / Sn4P3@C-CMC-Na material can be better maintained during the charge and discharge process. In the subsequent CV cycle, the peak migrated to 0.8V, and the position of appearance was consistent with that of the Sn3P4 / Sn4P3-PVDF negative electrode. Subsequently, a sharp reduction peak corresponding to the generation of SEI appeared near 0.4V. This peak shifted to the left low voltage area relative to the SEI reduction peak of the Sn3P4 / Sn4P3-CMC-Na negative electrode. The reduction peak that appeared at 0.18V corresponds to the further reaction of Li2Sn3P4 to generate Li3P and Li 4.4 Sn alloy, in the subsequent CV cycle, this peak splits into two reduction peaks, one at 0.25 V, which corresponds to Li 4.4 The oxidation peaks at 0.55V and 0.83V correspond to the formation of Sn alloy, and the other at 0.50V corresponds to the formation of Li3P. 4.4 The dealloying process of Sn and the decomposition reaction of Li3P.
[0059] The Sn3P4 / Sn4P3@C-CMC-Na electrode prepared in this example was subjected to a cycle stability test at a voltage range of 0.005-1.2 V and a current of 0.1 A g -1 After 100 cycles under the same conditions, the cycle stability performance diagram is shown in the figure below. Fig.12 As shown in (a), Fig.12 (a) It can be seen that the discharge capacity of Sn3P4 / Sn4P3@C-CMC-Na negative electrode in the first cycle is 1512 mA h g -1 , charging capacity is 1195mA hg -1The first cycle coulombic efficiency is 79%. Compared with Example 2, the 81% of the Sn3P4 / Sn4P3-CMC-Na electrode is slightly lower. Although the coulombic efficiency is reduced, the Sn3P4 / Sn4P3@C-CMC-Na negative electrode shows better cycle capacity. After 100 cycles, it maintains a higher discharge / charge capacity of 557 mA h g -1 and 542mA hg -1 Compared with Sn3P4 / Sn4P3-CMC-Na negative electrode, it has increased by more than 200mA hg -1 The capacity of Sn3P4 / Sn4P3-CMC-Na negative electrode is 36% of the first cycle discharge capacity (25% for Sn3P4 / Sn4P3-CMC-Na negative electrode). The Sn3P4 / Sn4P3@C-CMC-Na electrode has good electrochemical performance and better cycle stability. This is mainly because, based on the action of the aqueous binder CMC-Na with good ductility and lasting stress adaptability, the presence of carbon black Super P improves the conductivity of the overall electrode and further accelerates the transport rate of ions and electrons. In addition, it is evenly coated on the surface of the layered Sn3P4 / Sn4P3 material, better maintaining the morphology of the material during the cycle, alleviating the collapse of the 2D structure, and greatly improving the stability of the material, so that the lithium storage potential of the 2D structure Sn3P4 / Sn4P3 material has been effectively exerted, so Sn3P4 / Sn4P3@C-CMC-Na has better cycle performance.
[0060] The Sn3P4 / Sn4P3@C-CMC-Na electrode prepared in this example was subjected to a cycle stability test with a voltage range of 0.005-1.2 V and a current of 0.1 A g in the first three cycles. -1 , then 1A g -1 Under these conditions, the obtained cycle stability performance diagram is shown in Fig.12 As shown in (b), analysis 12(b) shows that the Sn3P4 / Sn4P3@C-CMC-Na negative electrode has a -1 The Sn3P4 / Sn4P3@C-CMC-Na was activated for 3 cycles under low current. The first cycle discharge capacity was 1484 mA hg -1 , the discharge capacity in the third cycle is 1020mA hg -1 When the current increases to 1A g -1 When the discharge capacity of Sn3P4 / Sn4P3@C-CMC-Na negative electrode drops to 958 mA h g -1 , with less attenuation, the Sn3P4 / Sn4P3-CMC-Na electrode dropped to 718 mA hg -1 , Sn3P4 / Sn4P3-PVDF electrode dropped to 120mA hg -1After 100 cycles, 513 mA hg -1 、502mA hg -1 The high discharge / charge capacity was maintained in the fourth cycle (the current was increased to 1A g -1 ) discharge capacity. The Sn3P4 / Sn4P3@C-CMC-Na electrode showed the best high current carrying capacity. This proves that even at high current, the Li + It can also perform well in the deintercalation reaction. This is due to the unique layered structure of the material, the water-based binder, and the carbon black Super P, which provide a fast transport path for ions, good adhesion, and high conductivity.
[0061] The Sn3P4 / Sn4P3@C-CMC-Na electrode prepared in this example was subjected to rate performance test. -1 , 0.2A g -1 , 0.5A g -1 , 1A g -1 , 2A g -1 The charge and discharge capacity performance under current, the rate performance diagram obtained by cycling 5 times at each current is as follows Fig.13 As shown in the figure, it can be seen that compared with the two electrodes of Example 2 and Comparative Example 1, which showed a step-like rapid decline in the first ten cycles, the attenuation trend of the Sn3P4 / Sn4P3@C-CMC-Na electrode was greatly weakened, showing the best rate performance. -1 , 0.2A g -1 , 0.5A g -1 , 1A g -1 The discharge capacity under current is 1173mA hg -1 、1085mA hg -1 、968mA hg -1 、859mA hg -1 When the current increases to 2A g -1 , the electrode maintains 750mA hg -1 The discharge capacity of Sn3P4 / Sn4P3-CMC-Na electrode is 171mA h g -1 Sn3P4 / Sn4P3-PVDF electrode has only 2mA hg -1 When the current returns to 0.1A -1 , its discharge capacity is 976mA hg -1, showing the best recovery ability. This proves that the Sn3P4 / Sn4P3@C-CMC-Na electrode has the best rate capability among the three electrodes, the internal polarization of the battery is small, and the charging and discharging process is more stable and complete.
[0062] Comparative Example 1
[0063] 1. Use an electronic balance to weigh 0.14 g of Sn3P4 / Sn4P3 prepared in Example 1, 0.04 g of carbon black Super P, and 0.02 g of PVDF binder. After weighing, transfer them to a mortar, add 5 mL of NMP, grind by hand, mix well, and obtain a uniform and viscous slurry;
[0064] 2. Clean the copper foil with anhydrous ethanol, transfer the slurry to the copper foil, use a four-sided preparation device and select an appropriate thickness according to the viscosity, and evenly coat the slurry on the copper foil. Then put the copper foil coated with the film in a vacuum drying oven, bake it in air at 80°C for 2 hours without vacuuming to prevent wrinkles in the film, and then bake it at 80°C under vacuum conditions for 12 hours. After drying, use a manual buckle machine to make the copper foil into a circular electrode sheet with a diameter of 12 mm, recorded as Sn3P4 / Sn4P3-PVDF electrode sheet, and use an electronic balance to weigh and record the mass of each Sn3P4 / Sn4P3-PVDF electrode sheet.
[0065] The Sn3P4 / Sn4P3-PVDF electrode prepared in this comparative example was tested by cyclic voltammetry with a voltage range of 0.005-1.2 V and a scan rate of 0.1 mV s -1 Before testing, the battery was left to stand for 24 hours to allow the electrolyte inside the battery to evenly infiltrate other components and eliminate polarization to obtain accurate measurement results. The resulting cyclic voltammetry curve is shown in Fig.14 As shown, analysis Fig.14 The CV curve of the Sn3P4 / Sn4P3-PVDF electrode shown in the figure shows a relatively gentle reduction peak at around 0.8V during the first discharge cycle. This peak corresponds to the Li + The embedding process generates Li2Sn3P4, but the peak is not particularly obvious, indicating that Li +The embedding process was not ideal and complete. It was then observed that a wide range of sharp reduction peaks appeared at 0.52V, but this peak only appeared in the first cycle and disappeared in the subsequent CV cycles, confirming that the peak corresponds to the formation of solid electrolyte (SEI) film in LIBs. The reduction peak at 0.25V is that the Li2Sn3P4 material continues to react with Li, corresponding to the formation of tin-lithium alloy and lithium phosphide. After the first CV cycle, the area changes between the subsequent CV cycle curves are large, proving that the capacity of the Sn3P4 / Sn4P3-PVDF negative electrode is severely attenuated and the cycle reversibility is poor, especially the first three cycles have the largest area change, proving that there is a lot of capacity loss in the first three cycles. Because the oxidation peaks and reduction peaks in the CV cycle are not particularly obvious, most of them are smooth curves.
[0066] The Sn3P4 / Sn4P3-PVDF electrode prepared in this comparative example was subjected to a cycle stability test at a voltage range of 0.005-1.2V and a current of 0.1A. -1 Under these conditions, the obtained cycle stability performance diagram is shown in Fig.15 As shown in (a), analysis Fig.15 (a) It can be seen that the discharge capacity of Sn3P4 / Sn4P3-PVDF negative electrode in the first cycle is 1429 mA h g -1 , charging capacity is 1057mA hg -1 , corresponding to the first cycle coulombic efficiency of 74%, the loss of the first cycle irreversible capacity is due to the formation of SEI film. At this current, the high first cycle discharge capacity of Sn3P4 / Sn4P3 material is mainly due to the high theoretical capacity of phosphorus in Sn3P4 / Sn4P3 material, and the heterojunction structure allows Sn3P4 and Sn4P3 to synergistically store Li + However, after 100 cycles, the Li + During this process, the negative electrode capacity dropped sharply and only maintained 65 mA hg -1 and 65mA hg -1 This is a very low discharge / charge capacity because the Sn3P4 / Sn4P3 material in the PVDF binder has a serious volume expansion and structural damage during the cycle. + The obstruction of the intercalation and deintercalation process leads to severe polarization and inability to fully charge and discharge, resulting in poor cycle stability.
[0067] The Sn3P4 / Sn4P3-PVDF electrode prepared in this comparative example was subjected to a cycle stability test with a voltage range of 0.005-1.2 V and a current of 0.1 A g in the first three cycles. -1 , then 1A g -1 Under these conditions, the obtained cycle stability performance diagram is shown in Fig.15 As shown in (b), analysis Fig.15 (b) It can be seen that, first, the Sn3P4 / Sn4P3-PVDF electrode has a -1 After 3 cycles of activation under current, the discharge capacity in the first cycle was 1356 mA hg -1 In the third cycle, there is still more than 300mA hg -1 However, when the current is increased to 1A g -1 The discharge capacity of Sn3P4 / Sn4P3-PVDF negative electrode decays to 120mA hg -1 This is because high current will affect Li + After 100 cycles of charge and discharge, 51mA hg -1 、51mA hg -1 It can be analyzed that the cycle performance of Sn3P4 / Sn4P3-PVDF electrode is -1 The electrode exhibits poor high current cycling performance, which also indicates that the lithium storage potential of Sn3P4 / Sn4P3 materials with layered morphology cannot be fully utilized when using PVDF binder.
[0068] The Sn3P4 / Sn4P3-PVDF electrode prepared in this comparative example was tested for its rate performance at 0.1A g -1 , 0.2A g -1 , 0.5A g -1 , 1A g -1 , 2A g -1 The charge and discharge capacity at the same current was cycled 5 times at each current and then recovered to 0.1A g -1 The obtained rate performance diagram is as follows Fig.16 As shown. Fig.16 It can be seen that the charge and discharge reversible capacity of the Sn3P4 / Sn4P3-PVDF negative electrode decreases in a step-by-step manner. -1 , 0.2A g -1 , 0.5A g -1 , 1A g -1 The discharge capacity under current is 671mA hg -1 、245mA hg -1 、57mA hg -1 、9mA hg -1 When the current increases to 2Ag -1 When the discharge capacity is very low, it is 2mA hg -1This is because when the current increases, the internal polarization of the battery becomes more serious, resulting in incomplete charging and discharging of the battery, and the large current affects the structure of the material, resulting in capacity decay. Subsequently, when the current returns to 0.1A g -1 , discharge capacity is 256mA hg -1 This indicates that the Sn3P4 / Sn4P3-PVDF electrode has poor rate performance.
Claims
1. Application of a heterojunction phosphorus / tin / carbon composite material, characterized in that The heterojunction phosphorus / tin / carbon composite material is prepared by the following method: S1. Evenly mix tin powder and phosphorus powder in a molar ratio of 3:4 to obtain a mixed powder, place the mixed powder in a quartz tube under vacuum, seal the quartz tube, place the quartz tube in a high-temperature tube furnace for high-temperature solid-phase reaction, heat the temperature to 420-460°C by a gradient program heating method, and heat the temperature at a rate of 2-3°C / min, and keep the temperature at 420-460°C for 3-7 days. After the reaction is completed, directly take out the quartz tube for quenching and cooling, take out the solid matter in the quartz tube, and obtain a phosphorus / tin composite material; the phosphorus / tin composite material is Sn3P4 / Sn4P3, the main phase is Sn3P4, and also includes Sn4P3; S2. In an inert gas atmosphere, the phosphorus / tin composite material and the conductive carbon black are mixed and ball-milled, wherein the mass ratio of the phosphorus / tin composite material to the conductive carbon black is 7:3 to 9:
1. After the ball-milling is completed, the mixture is allowed to stand to reduce the activity of the mixture. After the standing is completed, a heterojunction phosphorus / tin / carbon composite material is obtained; The heterojunction phosphorus / tin / carbon composite material is used to prepare a negative electrode for a lithium ion battery. The preparation method of the negative electrode for a lithium ion battery is as follows: The heterojunction phosphorus / tin / carbon composite material, conductive carbon black and aqueous binder sodium carboxymethyl cellulose solution are uniformly mixed, and the mass ratio of the heterojunction tin phosphide composite material, conductive carbon black and aqueous binder sodium carboxymethyl cellulose solution is 7:2:1 to obtain electrode slurry, and the electrode slurry is coated on copper foil and dried to obtain the lithium ion battery negative electrode.
2. The use of the heterojunction phosphorus / tin / carbon composite material according to claim 1, characterized in that: The standing time is 15 to 24 hours.
3. The use of the heterojunction phosphorus / tin / carbon composite material according to claim 1, characterized in that: In the ball milling operation, the ball milling is performed to a particle size distribution of 10 to 20 μm.
4. The use of the heterojunction phosphorus / tin / carbon composite material according to claim 1, characterized in that: The mass percentage concentration of the aqueous binder sodium carboxymethyl cellulose is 2-3%.
Citation Information
Patent Citations
Stannic phosphide / graphene composite cathode material for sodium-ion battery and preparation method thereof
CN105006551A
Lithium-ion / sodium-ion battery composite negative electrode material, negative electrode and battery
CN108417805A
Preparation method of large-dimension granular tin phosphide compound
CN109534308A
Method for preparing Sn3P4 rivet used for sodium-ion negative electrode material in carbon skeleton composite material
CN110071268A
Preparation method of Sn3P4 induced two-dimensional black phosphorus crystals
CN111285339A